Experience of living with cancer and comorbid illness: protocol for a qualitative systematic review. Issue 5 (9th May 2017) - Cavers, Debbie; Cunningham-Burley, Sarah; Watson, Eila; Banks, Elspeth; Campbell, Christine
Abstract : Introduction: There are an increasing number of people living with and beyond cancer, whose experience is further complicated by additional long-term health conditions in the context of an ageing population. The supportive care needs of this growing patient group should be recognised and addressed. There is a need to explore the experience of living with cancer and comorbid illness in order to develop optimal models of patient-centred care. This protocol describes a systematic review that aims to identify the qualitative evidence relating to the experience of cancer and comorbid illness for patients, informal carers and professionals, and to highlight areas where more research is needed. Methods and analysis: A systematic review following PRISMA guidance will be undertaken. Medline, Embase, CINAHL, PsycINFO, ASSIA, Sociological Abstracts, Web of Science, SCOPUS, OpenGrey and ProQuest Dissertations and Theses Global databases will be systematically searched for articles relevant to patient, carer and professional experiences. Two independent reviewers will screen articles for inclusion and evaluate them according to the Critical Appraisal Skills Programme tool. Extracted data will be combined using recognised methods of qualitative synthesis to offer new insights into the topic area and for a patient-centred model of care. Ethics and dissemination: The review does not require formal ethical review as no direct patient contact or patient identifiable data is used. Conduct of the review has been approved internally by the University of Edinburgh Centre for Population Health Sciences Ethics Review Committee. Results of the review will be published in a generalist peer-reviewed journal and presented at a relevant conference in addition to informing subsequent empirical work by the authors on this topic area.